Hermann Neubacher's mission to Serbia in 1943: Germany's search for politico-military solutions in the Balkans - Zorić Mirjana (Војно дело, 2014)
The Balkan region as a whole, especially Serbia as its strategic axis, has always been a target of various geopolitical schemes, which often led to war conflicts in the past. On the eve of the 70th anniversary of the liberation of Serbia in the World War Two, this paper analyzes Serbia from the perspective of the German command and the measures undertaken in the second half of the war in order to keep the Balkans, at a time when Germany was largely losing out on other European battlefields. This paper discusses the military and political aspects of the German strategy in the Balkans in 1943 and 1944, and the attempts to match, using political action (via Neubacher's mission) in Serbia and other Balkan countries, the changing strategic relations in Europe, caused by the defeat of the Wehrmacht at Stalingrad and in North Africa late in 1942 and early in 1943, and to restore the shattered German positions in its southeast, especially at a time when the World War Two was nearing its end.